Digitization Of Education Management: A Study On The Implementation Of EMIS In Supporting Strategic Decision-Making In The Ministry Of Religion - Hayyin Misro Ihtada; Walid Fajar Antariksa (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The purpose of this study is to analyze the implementation of the Education Management Information System (EMIS) at the Ministry of Religious Affairs in Pasuruan City as a decision-making support tool. This research employs a qualitative approach using observation, interviews, and documentation as data collection methods. The findings indicate that EMIS, as an official program of the Directorate General of Islamic Education, has been implemented through socialization activities, technical guidance, data collection, and data validation procedures. Data management through EMIS produces accurate, up-to-date information that plays a crucial role in decision-making, including the issuance of operational permits and the distribution of aid. Supporting factors for EMIS implementation include internet access, technological devices, and collaboration among operators. Meanwhile, the main obstacles consist of limited human resources, difficulties in data collection, and technical server issues, all of which need to be addressed to enhance the system's overall effectiveness.